A protein domain-oriented approach to expand the opportunities of therapeutic exon skipping for USH2A-associated retinitis pigmentosa - Renske T.W. Schellens; Sanne Broekman; Theo Peters; Pam Graave; Lucija Malinar; Hanka Venselaar; Hannie Kremer; Erik De Vrieze; Erwin Van Wijk (Elsevier, 2023)
Loss-of-function mutations in USH2A are among the most common causes of syndromic and non-syndromic retinitis pigmentosa (RP). We previously presented skipping of USH2A exon 13 as a promising treatment paradigm for USH2A-associated RP. However, RP-associated mutations are often private, and evenly distributed along the USH2A gene. In order to broaden the group of patients that could benefit from therapeutic exon skipping strategies, we expanded our approach to other USH2A exons in which unique loss-of-function mutations have been reported by implementing a protein domain-oriented dual exon skipping strategy. We first generated zebrafish mutants carrying a genomic deletion of the orthologous exons of the frequently mutated human USH2A exons 30-31 or 39-40 using CRISPR-Cas9. Excision of these in-frame combinations of exons restored usherin expression in the zebrafish retina and rescued the photopigment mislocalization typically observed in ush2a mutants. To translate these findings into a future treatment in humans, we employed in vitro assays to identify and validate antisense oligonucleotides (ASOs) with a high potency for sequence-specific dual exon skipping. Together, the in vitro and in vivo data demonstrate protein domain-oriented ASO-induced dual exon skipping to be a highly promising treatment option for RP caused by mutations in USH2A.